ANTESEDEN DAN KONSEKUENSI SINISME PADA LAYANAN APLIKASI DARING ALODOKTER - Frederikus Bramantyo; Didik Setyawan; Finisha Mahaestri Noor (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the effect of antecedents and consequences of cynicisim when use Alodokter application. The level of individual cynicism towards the Alodokter application was identified due to anxiety, negative emotions, and security in us e Alodokter application. Cynicism has an impact on attitudes toward failure and attitudes toward learning in use of online application. Data were collected through questionnaires that distributed to users of the Alodokter application. This study sample was 200 user Alodokter application. The sampling technique used was convenience sampling. These were analysed using SEM (Structural Equation Modeling) analysis with path analysis method. The results in this study indicated that all of hypotheses are supported. Cynicism has a positive effect on attitudes toward failure and negative effect on attitudes towards learning. The anxiety variable has a positive effect on cynicism, the variable of negative emotions has a positive effect on cynicism, and security has a negative effect on cynicism. Pat analysis method gives the result that cynicism has a mediating role in this study. It`s means that the antecedent variables of cynicism consist of anxiety, negative emotions, and security requi re cynicism as an evaluation of individuals to form attitudes toward failure and attitudes toward learning to take the further action.